FILSAFAT FEMINISME DAN IMPLIKASINYA DALAM BIMBINGAN KONSELING - Ahmad Yusuf (Jurnal Panrita, 2024)
This article uses a literature review research method to explore feminist philosophy and its implications in counseling guidance. Through analysis of various relevant literary sources, the author attempts to identify and summarize feminist thinking and its application in the context of counseling guidance. This method allows the author to explore information from various perspectives, so as to provide a comprehensive picture of the topic discussed. This literature review involves collecting data from journals and articles related to feminist philosophy and its implications in guidance and counseling. The data collection process begins with identifying relevant sources. Several academic databases such as Google Scholar, JSTOR, and ProQuest were used to search for scientific articles discussing feminist philosophy and its implications in counseling guidance. Data analysis was carried out by classifying information based on themes that emerged from the literature reviewed. Each theme is analyzed in depth to gain better insight into feminist philosophy and its implications in guidance counseling. The results show that feminist philosophy has significant implications in counseling guidance, both in terms of theory and practice. A gender-based approach in counseling does not only pay attention to individual experiences, but also considers the broader social context that influences the client's life. Through a gender-sensitive approach, guidance and counseling can contribute to women's empowerment and achieving gender equality in society.